Cooper Screening of Information Processing (C-SIP). Administrator's Manual - Cooper, Richard; Center for Alternative Learning, Havertown, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
This document is designed to assist individuals administering the Cooper Screening of Information Processing (C-SIP), which is intended as a diagnostic teaching tool that allows teachers or others to determine, in a conversational setting, whether a person manifests any common characteristics of learning problems. After a brief introduction, a Quick Start section is provided for individuals who prefer to try using the test before reading about it in detail. The remainder of the guide is an in-depth explanation of the C-SIP that is organized according to the C-SIP's actual section headings, which are titled as follows: "Educational History"; "Attention"; "Motor Skills"; "Auditory"; "Right/Left Discrimination"; "Organizational Skills"; "Employment"; "Emotional"; "Social and Family"; "Oral Communication"; "Writing"; "Handwriting"; "Basic Math Skills"; "Math Skills; "Math Vocabulary"; "Reading"; "Reading Comprehension"; "Vocabulary"; "Avoidance"; and "Goals" (an optional section). Each of the corresponding sections in the administrator's manual explains the following: the purpose of the given section of the C-SIP; things administrators should look for when asking the questions in the section; and special considerations in administering the questions in the given section to certain individuals (for example, individuals in certain age groups or with certain learning difficulties). The C-SIP test booklet is included. (MN)
Availability: Center for Alternative Learning, 6 E. Eagle Rd., Havertown, PA 19083. Tel: 610-446-6126.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Guides; Adult Education; Adult Learning; Elementary Secondary Education; Evaluation Methods; Guidelines; Information Processing; Learning Disabilities; Learning Problems; Screening Tests; Student Evaluation; 353 Project; Guides, Non-Classroom.; Tests/Questionnaires.